Upaya ASEAN Coordinating Centre for Humanitarian Assistance on Disaster Management dalam Penanganan Gempa Bumi Aceh Tahun 2016 - Andrian Alfi (2020)
This study aims to determine the role of the AHA Centre as a coordinating institution in the management of the earthquake disaster in Aceh in 2016. And also describes the stages during disaster management, such as the stage during the emergency response, and post-disaster. The type of research used is qualitative descriptive. The results showed that the role of the AHA Centre in Aceh through several stages, namely in the stage during the emergency response phase the AHA Centre acts as a communicator and facilitator in periodically announcing the status of conditions during the disaster, Mobilizing the ASEAN-ERAT Team to help BNPB evacuate disaster victims, sharing information about eartquake in Aceh by ADInet, and Facilitating logistical assistance from the Malaysia and Singapore in the form of family tents, Facilitating emergency tent assistance from DELSA (The Disaster Emergency Logistics System for ASEAN) to be distributed to several villages in Aceh. Coordinate assistance offered by international countries. Keywords: AHA Centre, Aceh, Earthquake Disaster 2016.